"I Think He Will Have It Throughout His Whole Life": Parent and Youth Perspectives About Childhood Mental Health Problems. (March 2018) - Schraeder, Kyleigh E.; Reid, Graham J.; Brown, Judith Belle
Children's mental health (CMH) problems can be long-lasting. Even among children and youth who receive specialized CMH treatment, recurrence of problems is common. It is unknown whether youth and their parents view the possibility of future mental health problems. This has important implications for how CMH services should be delivered. This grounded theory study gained perspectives from youth (aged 12–15 years) who received CMH treatment ( n = 10) and their parents ( n = 10) about the expected course of CMH problems. Three disorder trajectories emerged: (a) not chronic, (b) chronic and persistent, and (c) chronic and remitting, with the majority of youth falling in the third trajectory. A gap in available services between CMH and adult care was perceived by parents, leaving them either help hopeful or help hungry about their child's future care. Improving care for youth with ongoing mental health problems is needed to minimize costs to families and the system.